A Simple, Consistent Estimator for Disturbance Components in Financial Models - Levinsohn, James; MacKie-Mason, Jeffrey K. (The Review of Economics and Statistics, 1990)
James Levinsohn, Jeffrey K. MacKie-Mason, A Simple, Consistent Estimator for Disturbance Components in Financial Models, The Review of Economics and Statistics, Vol. 72, No. 3 (Aug., 1990), pp. 516-520